Evaluation of cytokine GDF15 as a biomarker of obesity - Orlando, Leonardo Claudio; Silva , Gabriel; Verza, Flávia Alves; Segura, Gabriela Gonzalez; Carita, Edilson Carlos; Fachin, Ana Lúcia; Marins, Mozart (Seven Editora, 2023)
The high calorie intake resulting from the increased consumption of processed foods, associated with the increase in physical inactivity, is a reflection of the economic and social development that shapes the lifestyle of humans today. Obesity and overweight are consequences of this lifestyle that have become a global public health problem and currently affect about 1.9 billion people worldwide. DOI:https://doi.org/10.56238/medfocoexplconheci-022